LANDSLIDE SUSCEPTIBILITY IN MUNICIPALITY WITH DIFFICULT ACCESS TO EMERGENCY SERVICES IN THS COPALITA SUBBASIN, OAXACA, MÉXICO. - Alanis Anaya, Rocio Marisol (Geographicalia, 2022)
In Mexico, landslides in areas with steep slopes and heavy rains cause obstruct roads, loss of infrastructure and even of human lives. Furthermore, in many communities, the roads are not adequate for the emergency services to be able to quickly attend to the damages. That is why this work evaluated the landslide susceptibility in the Copalita sub-basin in Oaxaca, through the weighting of cartographic variables associated with gravitational processes, in order to relate the supply of emergency services that can attend to the most susceptible municipalities and which are also difficult to access. The results of this work show that within the sub-basin there are not enough emergency services to deal with damages and, furthermore, response times can be up to six hours in the most remote communities.